2022
DOI: 10.1007/s11469-022-00828-8
|View full text |Cite
|
Sign up to set email alerts
|

Family Conflict and the Use of Conventional and Electronic Cigarettes in Adolescence: the Role of Impulsivity Traits

Abstract: Adolescents’ use of tobacco is a worldwide problem due to the negative consequences on their physical and psychosocial development. One contextual variable related to tobacco use is family conflict. Previous research has suggested that the relationship between family conflict and tobacco use could be mediated by personality traits. The aim of this study is to examine the direct and indirect effects of family conflict on tobacco use (conventional and electronic cigarettes) through specific impulsivity construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Several studies have highlighted the importance of considering the influence of family on suicidal behaviour in adolescents [22] as well as its influence on other problematic behaviours, such as alcohol [59], tobacco (traditional and electronic cigarettes) [60], and cannabis use [61]. Suicidal behaviour has also been associated with emerging problems, such as problematic internet use, in which the role of the family through parental control is particularly important [62].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the importance of considering the influence of family on suicidal behaviour in adolescents [22] as well as its influence on other problematic behaviours, such as alcohol [59], tobacco (traditional and electronic cigarettes) [60], and cannabis use [61]. Suicidal behaviour has also been associated with emerging problems, such as problematic internet use, in which the role of the family through parental control is particularly important [62].…”
Section: Discussionmentioning
confidence: 99%
“…Family conflict has been associated with more deleterious outcomes in adolescents and adults ( Rothenberg et al, 2017 ). Recent work also shows that family conflict mediates relations between impulsivity and early substance use ( Wang et al, 2021 ), whereas others, using cross sectional data, have also found that impulsivity mediates relations between family conflict and tobacco use among adolescents ( Eslava et al, 2022 ). Further, the majority of the literature on the impact of parental mental health on children’s health outcomes has largely focused on maternal depressive symptoms, which has resulted in a “mother-bashing” quality to the literature ( Downey and Coyne, 1990 ), providing an incomplete picture of family dynamics ( Ramchandani and Psychogiou, 2009 ; Pierce et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%